Relationships between soil fertility, banana weevil and nematodes in the East African highland cooking banana in Ntungamo, southwestern Uganda - Gold, C.; Speijer, P.; Ssali, H.; Karamura, E.B.; Okech, S. (International Society for Horticultural Science, 2000)
East African highland cooking bananas (Musa spp., AAA) are one of the most important staples in the Great Lakes region of Africa. It has been hypothesized that land use intensification within the region has led to decline in soil fertility, increased pest pressure, and decline in production. To document these relationships, a diagnostic survey was undertaken in Kikoni Parish, Ntungamo, southwestern Uganda, at a site where banana productivity is low (mean bunch weights of 14-23 kg per farm). The results showed that the soils were generally sandy loam. The soil pH 6.2 was within the suitable range for banana production but soil organic matter was generally low for most of the farms (3.1-4.5%). Foliar analysis indicated that K was generally below the recommended critical nutrient levels (CNL). Soil nutrient contents were 3% N, 0.22% P, 1.11% K, 0.40% Mg and 2.67% Ca. The banana weevil (Cosmopolites sordidus) was present in all the farms but damage was variable. The corm damage by weevil ranged from 1.2 to 8.4% on the inner cylinder and 4.5 to 9.9% on the outer cylinder. The survey also revealed that four species of nematodes, Helicotylenchus multicinctus, Pratylenchus goodeyi, Radopholus similis, and Meloidogyne spp. were present. P. goodeyi was the predominant species with highly varying densities per village (1200-1700 per 100 g roots for individual plants). However, root necrosis index was very low (< 10%). Weevil population density decreased with increase in foliar K/Mg and K/(K+Ca+MG) ratios, while root necrosis due to nematode damage declined with increase in the organic matter.